KESETARAAN GENDER DALAM PERCERAIAN: (Kajian Hadis tentang Gugat Cerai) - Misbahuzzulam; Umi Sumbulah; Fauzan Zenrif (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
This article explores aspects of gender equality in the context of divorce, with a study focus on the hadith that discuss divorce actions taken by women. This study aims to explore a deeper understanding of the Islamic view of divorce initiated by women and its impact on gender equality in society. By detailing the various relevant hadiths, the study analyzes the context, law, and wisdom behind the ruling. The results of this study show that women can terminate their marriage by filing a khul' (sue for divorce) before a religious court. With this, it is hoped that every married couple has the awareness to carry out their duties and treat their spouses well, so that the harmony and integrity of the household can be maintained.